(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To determine the status of estrogen and the progesterone receptor among pre-menopausal and post-menopausal women with breast cancer Background: Women all around the world are most commonly hit by the malignancy named the “breast cancer”. About one fifth of women in the world die due to this as its incidence is continuously increasing. Age, age at menarche, parity, age at menopause are few of the risk factors responsible. Age and menopause are the two factors which affects the overall influence the ER/ PR status. Because of clear evidence that investigation of the estrogen receptor (ER) expression reveals clue for the biologic and prognostic progression of disease. Materials And Methods: A cross sectional study was conducted at surgical Unit-III, Chandka Medical College Hospital, Larkana, using tissue sample biopsy 120 patients were evaluated to determine the estrogen receptor (ER) status. Statistical package for social sciences (SPSS) version 25 was used to enter and analyze the data. Results: In this study, the postmenopausal women were 87 (72.5%) while premenopausal were 33 (27.5%) in this study Main outcome of the study was ER/PR status which was found that among postmenopausal women ER and PR were positive in 77% (n =67) & 79.3% (n = 69) respectively while among premenopausal women ER and PR were positive in 97% (n =32) & 69.7% (n = 23) respectively Conclusion: The results show that nearly three fourths of all breast cancer affected patients had an ER and PR were positive- while majority of these were postmenopausal women. Education & awareness, screening & early detection and proper and quick treatment response to ER/PR positive and all other subtypes of breast cancer are the key to better prognosis.